Citizenship and ecological education: Exploring the role of the Enzim Bakti community in raising ecological awareness - Prini Desima Evawani Ambarita; Cecep Darmawan; Rahmat Rahmat; Syaifullah Syaifullah (Jurnal Civics: Media Kajian Kewarganegaraan)
This study aims to investigate the role of Enzim Bakti Community in raising ecological awareness through citizenship education, using a case study as the main approach. Enzim Bakti Community is a community organization that focuses on ecological and social activities at the local level. This study uses a phenomenological method to describe how this community influences its members' understanding and behaviour regarding environmental issues. An in-depth case study was conducted to understand the concrete contribution of Enzim Bakti Community in educating its members about ecological and citizenship responsibilities. The study's findings show that through various activities such as tree planting, recycling campaigns, and environmental counselling, this community has created a deeper awareness of the importance of preserving the environment. The citizenship education implemented by Enzim Bakti Community broadens its members' knowledge about environmental issues and builds active involvement in promoting sustainability principles in their daily lives. Through discussions, training, and collaborative projects, community members learn to consider the ecological impacts of their actions and contribute to collective efforts to improve local environmental conditions. This study provides in-depth insights into how local communities can act as agents of social change in raising ecological and citizenship awareness. The implications of this study highlight the important role of civil communities in building a more environmentally conscious society and committed to collective action for a more sustainable future.